The formation of communication skills in the residents of General Comprehensive Medicine of the Turcios Lima Polyclinic of Pinar del Rio - Yoannia Rojas Castro; Juan Lázaro Márquez Marrero; Marvelia Díaz Calzada (Universidad Médica Pinareña, 2022)
Communication skills are necessary in clinical practice from the mere fact of analyzing the patient as an integral unit (bio-psycho, social, spiritual and cultural) and where optimal communication is guaranteed, for the sake of health promotion, disease prevention and timely therapy, as an essential element of a medical practice that recognizes the human being as a personality, which is registered in the model of the MGI professional. The research is oriented to the improvement of the formation of communicative skills in MGI residents of the Luis A Turcios Lima polyclinic of Pinar del Río. To achieve this, a strategy of this process was based on the principles of sequential and contextualized character; in which the skills to be trained are determined by abilities such as: apply, observe, identify, value, make, participate and execute, which respond to the professional's way of acting; all of which goes through the stages of orientation, execution and control and is structured through the didactic components that typify it as a process and as a result.